Developing an Understanding of English as a Global Language for a Business Setting - Briguglio, Carmela (Peter Lang, 2005)
This study of the linguistic practices in two multinational workplaces raises a number of questions concerning education for business communication in English. For instance, are we targeting the sorts of skills that higher education students will need in real multinational workplaces? And how do we prepare students for email communication, an extremely dynamic medium reflecting elements of both written and spoken language? Finally, what can we do to prepare higher education students, whether L 1 or L2 speakers of English, for greater tolerance of the different accents and varieties of English which they will inevitably meet in the global marketplace? These are issues which business schools around the world should be concerned with, for these are the linguistic skills with which employees in multinational workplaces will need to be equipped in the 21 st century. Such skills will be required not only by companies wishing to be successful, but also by employees themselves who see such linguistic skills as pre-requisites for advancement and promotion in the global workplace.